Introduction to Ghana's Oil Industry: History and Future Trends - Aryeetey, M. (University of Ghana, 2016)
Globally, Petroleum and petroleum products have become an essential part of the energy mix; and energy, in turn, has become the lifeblood of human existence. Without energy, our lives would be almost unrecognizable and industrialization will drastically grind to a halt. Over the last century, the demand for petroleum has greatly increased to the extent that it has become the most valuable commodity traded on world markets is proud to be part of an industry that truly powers economies. The global petroleum industry is usually divided into three major components: upstream, midstream and downstream. Until recent times, Ghana’s petroleum industry was defined by intermittent acquisition of data and drilling of wells offshore, mainly in the exploration phase with virtually no significant development activities (upstream sector), the importation of crude oil and petroleum products, a relatively small amount of crude refining, and the distribution of refined products, all at the downstream sector. The establishment of the Ghana National Petroleum Corporation (GNPC), an Agency under the Ministry of Petroleum in 1983was a bold step that produced the leadership that the local industry needed. GNPC as a national organization was charged with significant responsibilities in respect of petroleum exploration and production. The objectives of the Corporation include efficient exploitation of oil and gas resources within our territories, jobs creation, general economic development, economic and energy security, vertical integration and the maximization of shareholder value. Over the last 30 years GNPC have worked with the Government and other sister Agencies in restructuring and positioning the nascent industry for the big take off. From 1970 when the first offshore well was drilled and the first oil discovery was made in the Saltpond basin, to several marginal oil and gas discoveries made later on in the Tano basin, to the first deep-water well drilled by Phillips Petroleum in 900m of water in the Cape Three Points sub basin, and the extensive data acquisition offshore, Ghana had come a long way before our significant breakthrough in 2007. Finding new oil and gas reserves is not just about gaining rights to licenses and having access to capital and technology, but also about laws, regulations and permits established by authorities and by governments. It is also about forming and managing partnerships, negotiating complex deals and working with the complex geopolitics of the industry. The discovery of commercial quantities of oil and gas in deep-water offshore Ghana made it evident that the current legal and regulatory framework governing the industry is not robust enough to counter the challenges. The Government and other stakeholders therefore set out to tightened up framework to adequately protect the interest of Ghana and to ensure maximum benefits from the natural resource for the people of Ghana. The new E&P Bill (Act 919) is expected to introduce a lot of clarity and transparency in the industry. The story of the oil industry in recent times has not been very good. From late 2014 to date, oil projects around the globe, including Ghana, have suffered delays, cancellation and reduced investment as a result of the global slump in oil prices. This low oil price, if sustained, could mark the beginning of a long-term drop in upstream oil and natural gas investment. Ghana's case is worsened by the maritime border disputes with Cote D'Ivoire. The dispute has adversely affected operations in our most prospective sedimentary basin. However, as a country, Ghana is lucky to have in recent times two producing oil and gas field with a third expected to reach first oil early 2017. Going into the future, how do we ensure that our industry remains competitive and attractive to investment in these difficult periods of low capital? More importantly, how do we all ensure that the country maximizes the use of its share of the revenue from oil proceeds for the benefits of Ghanaians?
MICHAEL NII ARMAH ARYEETEY He is the Chief Operating Officer of the newly established GNPC Exploration & Production Company Limited (EXPLORCO). EXPLORCO is a subsidiary of the Ghana National Petroleum Corporation (GNPC) established in 2014 to serve as a strategic vehicle through which GNPC intends to build rapid local capacity and technology transfer as well as attain the goal of a world-class operator. As the Chief Operating Officer, he is responsible for managing EXPLORCO's interests in eight shallow and deep-water assets offshore Ghana. He also provides general oversight of all operational activities and supervises the day-to-day business of the Company. Professionally, he has over fifteen years of exploration and production experience that spans both the gold mining and oil and gas sectors of Ghana. His career with GNPC began in 2004 where he rose through the ranks to become the Lead Petroleum Geologist. He worked in the Geology Department of GNPC with responsibilities for oil block evaluation and promotion, license negotiations, and a technical support for the Corporate Strategy & New Business Unit. He also served as a member of the Jubilee Field Team from 2007 to 2012. Until his present appointment as Chief Operating Officer, Michael served on various Committees established by GNPC, Ministry of Energy and the Government of Ghana because of his knowledge of the Upstream Industry in Ghana. He has also presented Technical papers and featured on expert panel discussions in Ghana and at international conferences (USA, UK, France, South Africa, Italy, Nigeria, Morocco, etc.) and fora. He is currently a part-time Lecturer for the Geoscience Graduate Program at the Earth Science Department of the University of Ghana. Mr. Aryeetey holds a Bachelor’s Degree in Geology from the University of Ghana, and a Master of Science degree in Petroleum Geoscience from the NTNU, Norway.
Keywords: Oil Industry; Ghana; Future Trends